Peran orang tua dalam upaya menumbuhkan kecerdasan Emosional dan Spiritual (ESQ) pada anak menurut konsep Islam - Imron,; Afriantoni,; Afgani, Muhammad Win (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
This study aims to analyze emotional and spiritual intelligence in early childhood and the role of parents in fostering it. The potential for emotional and spiritual intelligence has existed since birth, but requires the active role of the family to develop optimally. The research uses descriptive qualitative methods with literature study techniques, referring to Islamic education literature and intelligence theory. The results show that emotional intelligence includes the ability to recognize feelings of self and others, motivate oneself, and manage emotions adaptively. Spiritual intelligence relates to the spiritual dimension in interpreting life through the principle of tawhid. The role of parents is crucial in providing education and training to develop this potential according to the child's nature, so that they grow into a complete human being according to Islamic values. This research confirms that the development of emotional and spiritual intelligence requires the synergy of lifelong learning, family education, and Islamic values. Abstrak Penelitian ini bertujuan menganalisis kecerdasan emosional dan spiritual pada anak usia dini serta peran orang tua dalam menumbuhkannya. Potensi kecerdasan emosional dan spiritual telah ada sejak lahir, namun memerlukan peran aktif keluarga untuk berkembang secara optimal. Penelitian menggunakan metode kualitatif deskriptif dengan teknik studi kepustakaan, mengacu pada literatur pendidikan Islam dan teori kecerdasan. Hasil penelitian menunjukkan bahwa kecerdasan emosional mencakup kemampuan mengenali perasaan diri dan orang lain, memotivasi diri, serta mengelola emosi secara adaptif. Kecerdasan spiritual berhubungan dengan dimensi rohani dalam memaknai kehidupan melalui prinsip tauhid. Peran orang tua sangat krusial dalam memberikan pendidikan dan latihan untuk mengembangkan potensi ini sesuai fitrah anak, sehingga tumbuh menjadi manusia yang utuh sesuai nilai-nilai Islam. Penelitian ini menegaskan bahwa pengembangan kecerdasan emosional dan spiritual membutuhkan sinergi pembelajaran seumur hidup, pendidikan keluarga, dan nilai keislaman.